Third Party Intervention:Strategi Tiongkok di Konflik Sudan Selatan - Fadhilah Putri, Erti (Hubungan Internasional Universitas Andalas, 2022)
This research explores and details some of the civil conflicts that occurred in South Sudan in 2013 and China strategy to seek a peace process that China has never done before. The intervention carried out by China today in civil conflict in South Sudan is an effort to bring the peace process known as third party intervention. This study adopted from third party intervention Ronald J. Fisher by using the contingency model as a tool to analyze the stages of intervention carried out by China in accordance with the conditions of the conflict that occurred. This study uses qualitative methods with secondary data collection techniques. The findings of this study indicate that China has an important role in the peace process in the civil conflict of South Sudan. China active role can be seen that China has taken several forms of interventions such as negotiation, mediation, power mediation, providing development assistance and special consultations. But China success in pursuing peace in South Sudan is when conflict conditions in the level of destruction of China carry outactions peacekeeping as a form of controlling violence and encouraging arbitration and consultation to realize a ceasefire. China success in pursuing peace is in line with the contingency modelthat offers the type of intervention that is suitable at the intervention stage in such conflict conditions. This shows the effectiveness of the contingency model in offering conflict resolution.